2021
DOI: 10.1111/josi.12447
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving teachers as procedurally just limits the negative effects of delinquent peer associations: An analysis of Australian adolescent boys’ and girls’ perceptions of school authority

Abstract: This research addressed whether perceptions of antisocial peers play a role in shaping individual perceptions of the legitimacy of school authority figures in young people. Using data from a sample of 102 young people from Brisbane, Australia, who participated in the Ability School Engagement Program, we examined whether associating with peers who engage in antisocial behavior was related to perceptions of the legitimacy of school authority over time. Mixed-effects linear regression analyses indicated that ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…Overall, the findings suggest that better and more fair relationships teachers in late childhood are associated with more positive attitudes towards the police during adolescence. This lends support to the notion that relationships and encounters with nonlegal authorities early in the life course form the basis for how youth later interact with and perceive legal authorities (e.g., Cardwell et al, 2021).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Overall, the findings suggest that better and more fair relationships teachers in late childhood are associated with more positive attitudes towards the police during adolescence. This lends support to the notion that relationships and encounters with nonlegal authorities early in the life course form the basis for how youth later interact with and perceive legal authorities (e.g., Cardwell et al, 2021).…”
Section: Discussionsupporting
confidence: 58%
“…Teachers are key actors within this process, as the ways in which teachers treat children and apply rules send signals regarding the trustworthiness and fairness of authorities (e.g., Tyler & Trinkner, 2017 ). Prior research has shown that the quality of the relationship between teacher and child is associated with more positive perceptions of teacher or school authority (e.g., Caldwell et al, 2021 ; Gregory & Ripski, 2008 ; Gouveia-Pereira et al, 2017 ; Roberson, 2014 ). However, there has been relatively less attention to the processes that connect attitudes towards different sources of authority, such as between teachers and police (Forrest, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For both groups of youth, PJ clearly mattered. Consistent with the PJ framework (Tyler, 2017) and literature (e.g., Cardwell et al, 2021;Mazerolle et al, 2013;McLean et al, 2019), perceptions of fair and just treatment may enhance youths' willingness to cooperate with officers and their legal requirements (Walters & Bolger, 2019). To the extent that a youth feels as though their JPO encourages them to work collaboratively and treats them fairly and justly, they may feel more able to complete their probationary terms and conditions.…”
Section: Perceived Chances Of Successful Life Outcomesmentioning
confidence: 82%
“…As a framework, PJ has been applied to understand individuals’ reactions to various institutional practices, including those from schools, law enforcement, and the criminal legal system (Fine et al, 2022; Mazerolle et al, 2013). Across various contexts, PJ has been positively associated with compliance and cooperative behaviors (Cardwell et al, 2021; Fine et al, 2022; McLean et al, 2019).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Second, past research has only studied the TI phenomenon from an individual cognitive angle (e.g., classroom identification or belongingness; Jiang et al, 2018) or an interpersonal interaction-based approach (e.g., interpersonal or procedural justice; Cardwell et al, 2021). It has thus far neglected to tap the motivational effects of TI on student behavior.…”
Section: Discussionmentioning
confidence: 99%